Numerical simulation for fractional phi-4 equation using homotopy Sumudu approach. (8th February 2021) - Alomari, A.K.; Drabseh, Ghufran A.; Al-Jamal, Mohammad F.; AlBadarneh, Ramzi B.
In this study, we utilise the homotopy analysis method and the Sumudu transform to find the solution of fractional order partial differential equations. We focus primarily on the employment of the method for solving the fractional phi-4 equation in one-dimensional spatial domain. The method can be extended easily for more general nonlinear equations. Convergence and error analysis are given. Numerical experiments show that the method is both effective and accurate, and suits such type of applications.